2019
DOI: 10.1158/0008-5472.can-19-1504
|View full text |Cite
|
Sign up to set email alerts
|

SRSF3-Regulated RNA Alternative Splicing Promotes Glioblastoma Tumorigenicity by Affecting Multiple Cellular Processes

Abstract: Mis-regulated alternative RNA splicing (AS) contributes to the tumorigenesis and progression of human cancers, including glioblastoma (GBM). Here, we showed that a major splicing factor, serine and arginine rich splicing factor 3 (SRSF3) was frequently upregulated in clinical glioma specimens and that elevated SRSF3 was associated with tumor progression and a poor prognosis for glioma patients. In patient-derived glioma stem-like cells (GSCs), SRSF3 expression promoted cell proliferation, self-renewal, and tum… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
73
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(90 citation statements)
references
References 53 publications
(77 reference statements)
9
73
0
Order By: Relevance
“…The binding of hnRNPA1, hnRNPA2, and PTBP1 to sequences flanking exon 9 promotes the inclusion of exon 10 and expression of PKM2, thus ensuring high glycolytic flux in GBM cells [45,46]. Another splicing factor contributing to this metabolic switch is the SR protein SRSF3, which is also up-regulated in gliomas and sustains glioma stem cells (GSCs) growth, self-renewal, and tumorigenicity [47]. Whole transcriptome analysis revealed a role for SRSF3 as widespread modulator of gene expression and splicing in GBM ( Table 2).…”
Section: Splicing Dysregulation In Brain Tumorsmentioning
confidence: 99%
“…The binding of hnRNPA1, hnRNPA2, and PTBP1 to sequences flanking exon 9 promotes the inclusion of exon 10 and expression of PKM2, thus ensuring high glycolytic flux in GBM cells [45,46]. Another splicing factor contributing to this metabolic switch is the SR protein SRSF3, which is also up-regulated in gliomas and sustains glioma stem cells (GSCs) growth, self-renewal, and tumorigenicity [47]. Whole transcriptome analysis revealed a role for SRSF3 as widespread modulator of gene expression and splicing in GBM ( Table 2).…”
Section: Splicing Dysregulation In Brain Tumorsmentioning
confidence: 99%
“…Amiodarone's suppressive effects on the SRSF3 promoter activity were further veri ed in GBM8401 and U118MG glioma cell lines [6]. Numerous studies demonstrated that SRSF3 and miR-224 are frequently upregulated in glioma cells and are associated with tumor progression and a poor prognosis in glioma patients [32,33].…”
Section: Discussionmentioning
confidence: 98%
“…Functional mutations of SRSF2 drive the cancer genesis of hematopoietic cells [43]. SRSF3 is a multiple cancer related splicing factor, namely glioblastoma [44], colon cancer [45], oral squamous carcinoma [46], etc. Moreover, the expression of SRSF2/3 is signi cantly decreased in de novo AML patients in comparison with that of healthy controls.…”
Section: Discussionmentioning
confidence: 99%